Immunological Basis of Bone Marrow Failure after Allogeneic Hematopoietic Stem Cell Transplantation - Masouridi-Levrat, Stavroula; Simonetta, Federico; Chalandon, Yves (Frontiers in Immunology, 2016)
Bone marrow failure (BMF) syndromes are severe complications of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In this work, we distinguish two different entities, the graft failure (GF) and the poor graft function (PGF) and we review the current understanding of the interactions between the immune and hematopoietic compartments in these conditions. We first discuss how GF occurs as the result of classical alloreactive immune responses mediated by residual host cellular and humoral immunity persisting after conditioning and prevented by host and donor regulatory T cells. We next summarize the current knowledge about the contribution of inflammatory mediators to the development of PGF. In situations of chronic inflammation complicating allo-HSCT such as graft-versus-host disease (GvHD) or infections, PGF seems to be essentially the result of a sustained impairment of hematopoietic stem cells (HSC) self-renewal and proliferation caused by inflammatory mediators, such as interferon-γ (IFN-γ) and tumor necrosis factor-α, and of induction of apoptosis through the Fas/Fas Ligand pathway. Interestingly, the production of inflammatory molecules leads to a non-MHC restricted, bystander inhibition of hematopoiesis therefore representing a promising target for immunological interventions. Finally, we discuss immune-mediated impairment of bone marrow microenvironment as a potential mechanism hampering hematopoietic recovery. Better understanding of immunological mechanisms responsible for BMF syndromes after allo-HSCT may lead to the development of more efficient immunotherapeutic interventions.